Intersection rotational invariance regression based plant disease detection - J. Senthil; N. K. Karthikeyan; R. Senthilkumar (Plant Molecular Biology, 2026)

A Review on Potato Dormancy Prediction and Sprouting Detection Methods: Advancements in Analytical Technologies for Postharvest Physiology - T. Senthilkumar; S. Ramalingam; R. K. Goraya; U. C. Lohani; C. B. Singh (Potato Research, 2026)

Retraction notice to “Unearthing Earth's secrets: Exploring the environmental legacy of contaminants in soil, water, and sediments” [Environ. Res. 249 (2024) 118246] - Gautham Devendrapandi; Ranjith Balu; K. Ayyappan; Ramamoorthy Ayyamperumal; Salh Alhammadi; Mahimaluru Lavanya; R. Senthilkumar; P.C. Karthika (Environmental Research, 2026)

Isolation and complete genome analysis of Porcine Parvovirus 1 from swine with reproductive failure in southern India - P. Mohanapriya; S. Parthiban; K. Reshma; M. Parthiban; M. Murugan; A. Ramesh; K. Senthilkumar; P. Raja; P. Jalantha; Jagadish Hiremath; S. S. Patil; M. Kalyana Chakravarthi; et al. (Archives of Microbiology, 2026)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

The Impact Assessment of Mechanized Transplanting of Sugarcane Settlings Using Economic Surplus Approach - K. P. Saha; Dushyant Singh; T. Senthilkumar; S. P. Singh; Rajni Jain; Manoj Kumar; V. Bhushanababu (Sugar Tech, 2025)

Sustainable development of cement-bonded particle boards using coir fiber edge trims and grain granulated blast furnace slag (GGBS): mechanical, thermal, and economic evaluations - Arya Ashok; Kiranbaalaji Senthilkumar; Karingamanna Jayanarayanan; K. M. Mini (Innovative Infrastructure Solutions, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Anticancer potential of Calligonum comosum L.’Her. and Calligonum crinitum Boiss plants from United Arab Emirates - Wesam Khader; Mohamed K. Kayali; Tawfik M. Taj Eddin; Abdul Hadi S. S. S. Alameri; Mughair Abdul Aziz; Jaleel Kizhakkayil; Annadurai Senthilkumar; Ayesha S. Al Dhaheri; Abdul Jaleel (Advances in Traditional Medicine, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Nanoplastics in heat-sensitive food packaging: A review of migration, detection, health, and environmental impacts - Senthilkumar Palanisamy; Barani Kumar Saravana Kumar; Aishwarya Vetrivel; Rahul Jacob Michael; Nivethitha Babu; Sanjay Sharan Nallamuthu; Kokila Saravanan; Shanmugam Venkatachalam; Naveen Kumar R J; Gayathri Devi Selvaraju; Rajendran K. Selvakesavan; Jintae Lee; et al. (Food Control, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Tackling toxicity and stability using eco-friendly metal-halide ion substituted perovskite nanocrystals for advanced display color conversion - Maithili K. Rao; M. Selvakumar; M.G. Mahesha; Selvaraj Paramasivam; M.S. Santosh; S. Senthilkumar; Shiva Kant; Sami Rtimi (Chemical Engineering Journal, 2024)

Interactive behavior of cadmium ions onto polyethylene microplastics in aquatic system - D. M. Reddy Prasad; B. S. Naveen Prasad; R. Senthilkumar; K. Saravana Kumar; S. Manickkam (International Journal of Environmental Science and Technology, 2024)

Genetic diversity studies between Ipomoea wild species and cultivated sweet potato (Ipomoea batatas (L.) Lam.) using SSR markers - M.S. Amritha; O.G. Dhanya; Aswathy G.H. Nair; P. Vidya; Senthilkumar K. Muthusamy; C. Mohan (South African Journal of Botany, 2024)

Elucidation of novel drought-responsive genes from tuber transcriptome of cassava under water deficit stress - A.V.V. Koundinya; Senthilkumar K. Muthusamy; B.R. Ajeesh; C. Mohan; J. Sreekumar; Sowmya Pulapet; Kesavan Markkandan; M.N. Sheela (South African Journal of Botany, 2024)

RETRACTED: Unearthing Earth's secrets: Exploring the environmental legacy of contaminants in soil, water, and sediments - Gautham Devendrapandi; Ranjith Balu; K. Ayyappan; Ramamoorthy Ayyamperumal; Salh Alhammadi; Mahimaluru Lavanya; R. Senthilkumar; P.C. Karthika (Environmental Research, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Engineering of hollow mesoporous Fe-graphitic carbon Nitride@CNTs for superior electrocatalytic oxygen reduction reaction - Anuj Kumar; Ram K. Gupta; Mohd Ubaidullah; Abdullah M. Al-Enizi; Bidhan Pandit; Senthilkumar Nangan; V. Jagadeesha Angadi; Ghulam Yasin (Fuel, 2024)

Genetic diversity analysis of Indian Cassava (Manihot esculenta Crantz) accessions using morphological and molecular markers - Swathy Sivan; Arya K; Sheela M N; Revathi B S; Prakash Krishnan B S; Senthilkumar K Muthusamy (South African Journal of Botany, 2023)

Engraftment of Transplanted Buccal Epithelial Cells onto the Urethrotomy Site, Proven Immunohistochemically in Rabbit Model; a Feat to Prevent Urethral Stricture Recurrence - Akio Horiguchi; Masayuki Shinchi; Kenichiro Ojima; Yusuke Hirano; Toshihiro Kushibiki; Yoshine Mayumi; Kosuke Miyai; Ichiro Miura; Masaru Iwasaki; Vaddi Suryaprakash; Rajappa Senthilkumar; Senthilkumar Preethy; et al. (Stem Cell Reviews and Reports, 2023)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Molecular evidence of porcine circovirus 3 infection in swine: first report in southern India - S. Parthiban; A. Ramesh; G. Dhinakar Raj; Anbu Kumar Karuppannan; S. Hemalatha; M. Parthiban; Chintu Ravishankar; K. Senthilkumar; D. Balasubramaniyam (VirusDisease, 2022)

Reuse of Uncontrolled Burnt Bagasse Ash from Sugar Industries with Waste Rubber Powder in Construction: A Waste to Wealth Approach for Sugar Mills - K. S. Teja; R. Senthilkumar; G. Athira; A. Bahurudeen (Sugar Tech, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Identification of potential MTAs and candidate genes for juice quality- and yield-related traits in Saccharum clones: a genome-wide association and comparative genomic study - Shanmugavel Senthilkumar; K. K. Vinod; Selvaraj Parthiban; Prathima Thirugnanasambandam; Thalambedu Lakshmi Pathy; Nandita Banerjee; Thelakat Sasikumar Sarath Padmanabhan; P. Govindaraj (Molecular Genetics and Genomics, 2022)

Distribution and toxicity of Bacillus thuringiensis (Berliner) strains from different crop rhizosphere in Indo-Gangetic plains against polyphagous lepidopteran pests - G. K. Sujayanand; Mohd Akram; Aravind Konda; Ashish Nigam; Shripad Bhat; Jyotirmay Dubey; Krishna Kumar; Senthilkumar K. Muthusamy (International Journal of Tropical Insect Science, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

The role of disinfectants and sanitizers during COVID-19 pandemic: advantages and deleterious effects on humans and the environment - Kuldeep Dhama; Shailesh Kumar Patel; Rakesh Kumar; Rupali Masand; Jigyasa Rana; Mohd. Iqbal Yatoo; Ruchi Tiwari; Khan Sharun; Ranjan K. Mohapatra; Senthilkumar Natesan; Manish Dhawan; Tauseef Ahmad; et al. (Environmental Science and Pollution Research, 2021)

A novel human donor cornea preservation cocktail incorporating a thermo-reversible gelation polymer (TGP), enhancing the corneal endothelial cell density maintenance and explant culture of corneal limbal cells - Bhuvaneshwari Namitha; Munusamy Rajendran Chitra; Mathevan Bhavya; Periasamy Parikumar; Shojiro Katoh; Hiroshi Yoshioka; Masaru Iwasaki; Rajappa Senthilkumar; Mathaiyan Rajmohan; Ramalingam Karthick; Senthilkumar Preethy; Samuel J. K. Abraham (Biotechnology Letters, 2021)
Purpose McCarey-Kaufman’s (MK) medium and Optisol-GS medium are the most commonly employed media for human donor corneal preservation. In this study, we evaluated the preservation efficacy of discarded human donor corneas using a Thermo-reversible gelation polymer (TGP) added to these two media. Methods Thirteen human corneal buttons collected from deceased donors, which were otherwise discarded due to low endothelial cell density (ECD) were used. They were stored in four groups: MK medium, MK medium with TGP, Optisol-GS and Optisol-GS with TGP at 4 °C for 96 h. Slit lamp examination and specular microscopy were performed. Corneal limbal tissues from these corneas were then cultured using explant methodology one with and the other without TGP scaffold, for 21 days. Results MK + TGP and Optisol-GS + TGP preserved corneas better than without TGP, which was observed by maintenance of ECD which was significantly higher in Optisol-GS + TGP than MK + TGP (p-value = 0.000478) and corneal thickness remaining the same for 96 h. Viable corneal epithelial cells could be grown from the corneas stored only in MK + TGP and Optisol-GS + TGP. During culture, the TGP scaffold helped maintain the native epithelial phenotype and progenitor/stem cell growth was confirmed by RT-PCR characterization. Conclusion TGP reconstituted with MK and Optisol—GS media yields better preservation of human corneal buttons in terms of relatively higher ECD maintenance and better in vitro culture outcome of corneal limbal tissue. This method has the potential to become a standard donor corneal transportation-preservation methodology and it can also be extended to other tissue or organ transportation upon further validation.

Genome-wide identification of Ran GTPase family genes from wheat (T. aestivum) and their expression profile during developmental stages and abiotic stress conditions - Soham Choudhury; Mansi; Senthilkumar K. Muthusamy; Jasdeep C. Padaria; Monika Dalal (Functional & Integrative Genomics, 2021)

Development and validation of heat-responsive candidate gene and miRNA gene based SSR markers to analysis genetic diversity in wheat for heat tolerance breeding - Pradeep Sharma; Geetika Mehta; Shefali; Senthilkumar K. Muthusamy; Sanjay Kumar Singh; Gyanendra Pratap Singh (Molecular Biology Reports, 2021)

Stability of micro-tidal inlets along coastlines dominated by littoral drift - R. Senthilkumar; K. Murali; V. Sundar (Journal of Coastal Conservation, 2017)

Effects of PCB126 and PCB153 on telomerase activity and telomere length in undifferentiated and differentiated HL-60 cells - Xing Xin; P. K. Senthilkumar; Jerald L. Schnoor; Gabriele Ludewig (Environmental Science and Pollution Research, 2016)

Synthesis of novel 4-hydroxycoumarin derivatives: evaluation of antimicrobial, antioxidant activities and its molecular docking studies - M. Govindhan; K. Subramanian; K. Chennakesava Rao; K. Easwaramoorthi; P. Senthilkumar; P. T. Perumal (Medicinal Chemistry Research, 2015)

Risk modulation of GSTM1–GSTT1 interactions to head and neck cancer in tobacco users - K. P. Senthilkumar; R. Thirumurugan (Molecular Biology Reports, 2014)

Preliminary Analysis of Polycyclic Aromatic Hydrocarbons in Air Particles (PM10) in Amritsar, India: Sources, Apportionment, and Possible Risk Implications to Humans - Simerpreet Kaur; Kurunthachalam Senthilkumar; V. K. Verma; Bhupander Kumar; Sanjay Kumar; Jatinder Kaur Katnoria; C. S. Sharma (Archives of Environmental Contamination and Toxicology, 2013)

Methylobacillus rhizosphaerae sp. nov., a novel plant-associated methylotrophic bacterium isolated from rhizosphere of red pepper - M. Madhaiyan; S. Poonguzhali; M. Senthilkumar; D. Pragatheswari; K.-C. Lee; J.-S. Lee (Antonie van Leeuwenhoek, 2013)

Computational analysis of deleterious missense mutations in aspartoacylase that cause Canavan’s disease - K. Sreevishnupriya; P. Chandrasekaran; A. Senthilkumar; R. Sethumadhavan; V. Shanthi; P. Daisy; J. Nisha; K. Ramanathan; R. Rajasekaran (Science China Life Sciences, 2012)

Viral and bacterial aetiologies of epithelial ovarian cancer - S. Shanmughapriya; G. SenthilKumar; K. Vinodhini; B. C. Das; N. Vasanthi; K. Natarajaseenivasan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Gamma-radiation induced modifications in substrate specificity of glucose dehydrogenase and carbon source utilization pattern of phosphate-solubilizing Pantoea strains - Young-Keun Lee; M. Senthilkumar; Il Yun Jeong; K. Annapurna; K. Swarnalakshmi (Biotechnology Letters, 2011)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Hybrid performance for yield and yield components in cardamom (Elettaria cardamom Maton) - D. Prasath; M. N. Venugopal; R. Senthilkumar; N. K. Leela (Euphytica, 2009)

Effect of different level and source of copper supplementation on immune response and copper dependent enzyme activity in lambs - P. Senthilkumar; D. Nagalakshmi; Y. Ramana Reddy; K. Sudhakar (Tropical Animal Health and Production, 2009)

Biocontrol Potential of Soybean Bacterial Endophytes Against Charcoal Rot Fungus, Rhizoctonia bataticola - M. Senthilkumar; K. Swarnalakshmi; V. Govindasamy; Young Keun Lee; K. Annapurna (Current Microbiology, 2009)

Detection and Characterization of ACC Deaminase in Plant Growth Promoting Rhizobacteria - V. Govindasamy; M. Senthilkumar; V. Mageshwaran; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2009)

Purification and partial characterization of antifungal metabolite from Paenibacillus lentimorbus WJ5 - Young-Keun Lee; M. Senthilkumar; Jung-Hun Kim; K. Swarnalakshmi; K. Annapurna (World Journal of Microbiology and Biotechnology, 2008)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Purification and Partial Characterization of Antifungal Peptides from Soybean Endophyte-Paenibacillus sp strain HKA-15 - M. Senthilkumar; V. Govindasamy; P. Dureja; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2007)

Role of Antibiosis in Suppression of Charcoal Rot Disease by Soybean Endophyte Paenibacillus sp. HKA-15 - M. Senthilkumar; V. Govindasamy; K. Annapurna (Current Microbiology, 2007)

Arbuscular mycorrhizal morphology and dark septate fungal associations in medicinal and aromatic plants of Western Ghats, Southern India - T. Muthukumar; M. Senthilkumar; M. Rajangam; K. Udaiyan (Mycorrhiza, 2006)

Impact of Fermented Brown Rice with Aspergillus oryzae Intake and Concentrations of Organochlorine Pesticides in Blood of Humans from Japan - T. Takasuga; K. Senthilkumar; H. Tsuji; J. Nagayama (Bulletin of Environmental Contamination and Toxicology, 2006)

Restriction Enzyme Analysis of Indian Isolates of Egg Drop Syndrome 1976 Virus Recovered from Chicken, Duck and Quail - N. Senthilkumar; J.M. Kataria; Madhuri Koti; K. Dhama; B.B. Dash (Veterinary Research Communications, 2004)

Polychlorinated Dibenzo- p -Dioxins, Dibenzofurans, and Dioxin-Like Polychlorinated Biphenyls in Livers of Birds from Japan - K. Senthilkumar, N. Iseki, S. Hayama, (Archives of Environmental Contamination and Toxicology, 2002)

Analysis of rice mitochondrial genome organization using pulsed-field gel electrophoresis - P. Senthilkumar; K. K. Narayanan (Journal of Biosciences, 1999)

Butyltin Compounds in River Otters (Lutra canadensis) from the Northwestern United States - K. Kannan; R. A. Grove; K. Senthilkumar; C. J. Henny; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1999)

Occurrence of Butyltin Compounds in Tissues of Water Birds and Seaducks from the United States and Canada - K. Kannan; K. Senthilkumar; J. E. Elliott; L. A. Feyk; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1998)

Accumulation Features of Polychlorinated Biphenyls and Organochlorine Pesticides in Resident and Migratory Birds from South India - S. Tanabe; K. Senthilkumar; K. Kannan; A. N. Subramanian (Archives of Environmental Contamination and Toxicology, 1998)